Thalidomide Prevented and Ameliorated Pathogenesis of Crohn’s Disease in Mice via Regulation of Inflammatory Response and Fibrosis - Chen, Hongjin; Xu, Haixia; Luo, Lijiao; Qiao, Lichao; Wang, Yaohui; Xu, Minmin; Li, Youran; Zhu, Ping; Yang, Bolin (Frontiers in Pharmacology, 2019)
Crohn’s disease (CD) is a chronic, relapsing form of inflammatory bowel disease, seriously threatening human health. Thalidomide has been used for the treatment of CD. However, the effects and the possible mechanisms of thalidomide on CD are still unclear. Herein, our study demonstrated that thalidomide protected colon mucosa against trinitro-benzene-sulfonic acid (TNBS)-induced injury, diminished inflammatory infiltration and levels of IFN-, IGF-1, IL-6, IL-17, TNF-,while increased the levels of IL-10 and TGF-. Moreover, it reversed the intestinal fibrosis and inhibited the accumulated infiltration, down-regulated the expression of col1a2, col3a2, MMP-3, MMP-9, MMP-1, TGF-, -SMA, but up-regulated the expression of TIMP-1 and Vimentin. Although it could be observed that the effect of thalidomide administration in modeling was better than after modeling, there was no statistical difference between the two groups. The present study provided evidence that the therapeutic effect of thalidomide alleviated the inflammatory response and damage of colon tissue, mainly by restoring the imbalance of TH17/Treg cells and inhibiting intestinal fibrosis in TNBS-induced mice colitis.